Long-term effects of antihypertensive therapy on cardiovascular events and new-onset diabetes mellitus in high-risk hypertensive patients in Japan. Issue 9 (September 2018) - Liu, Jinliang; Yasuno, Shinji; Oba, Koji; Konda, Manako; Ichihara, Chikako; Kitao, Hiromi; Kuwabara, Yoshihiro; Ueshima, Kenji
Abstract : Objective: During the Candesartan Antihypertensive Survival Evaluation in Japan (CASE-J) trial, patients with hypertension who received amlodipine had similar cardiovascular risks as those who received candesartan. We conducted a post-trial study, the Candesartan Antihypertensive Survival Evaluation in Japan 10-year follow-up (CASE-J 10). This study aimed to confirm the long-term cardiovascular effects of candesartan and amlodipine. Methods: Case report forms were sent to CASE-J investigators who agreed to participate in the CASE-J 10. All the available information was retrospectively collected. The primary endpoint was a time-to-first event for a composite of cerebrovascular, cardiac, renal, and vascular events, and sudden death. Secondary endpoints included new-onset diabetes (NOD), cardiovascular mortality, and all-cause mortality. For each endpoint, treatment effect was compared on an intention-to-treat basis, according to previous randomization categories. Results: A total of 1313 patients' data have been updated. The 10-year Kaplan–Meier rates of the primary endpoint were 14.7% for candesartan and 14.8% for amlodipine. After adjusting for baseline characteristics, the rates for the primary endpoint were similar between the two treatments (hazards ratioadj = 0.99, 95% CI 0.82–1.20). Candesartan had a lower Kaplan–Meier rate of NOD than amlodipine (8.3 vs. 11.1%), and when adjusted for clinical factors, candesartan remained an independent predictor for NOD prevention (hazard ratioadj = 0.71, 95% CI 0.52–0.98). Conclusion: With more than 28 385 patient-years follow-up, we demonstrated that candesartan and amlodipine were comparable in reducing cardiovascular events in patients with high-risk hypertension. Additionally, our results may support candesartan's superiority in reducing NOD incidence compared with amlodipine even after the long-term follow-up. Abstract : Supplemental Digital Content is available in the text